Women’s Experiences of Social Reactions From Informal and Formal Supports: Using a Modified Administration of the Social Reactions Questionnaire - DePrince, Anne P. (Journal of interpersonal violence, 2021)
A growing literature links social reactions to disclosures of intimate violence to posttraumatic outcomes. The Social Reactions Questionnaire (SRQ), a widely used measure developed to assess social reactions, asks about reactions received from people generally. The ability to examine the impact of social reactions from specific groups of people—such as criminal justice personnel versus community-based providers—has become increasingly more important from both research and practice perspectives. For example, as sexual assault responses nationally have relied on community-coordinated models that involve both criminal justice and community-based systems, tools are lacking to systematically assess the impact of social reactions from criminal justice personnel and community-based providers on survivors. Using the SRQ, the current study asked women to report separately on reactions received from criminal justice personnel, community-based providers, and informal supports. We recruited a diverse community sample of women (N = 228, ages 18-63, 19% lesbian/bisexual, 44% ethnic minority) who experienced a sexual assault in the previous year and disclosed to the criminal justice system and/or a community-based provider. Multilevel analyses revealed considerable variability in the social reactions reported by women across criminal justice personnel, community-based providers, and informal supports. Analyses supported a seven-factor structure for the SRQ when the measure is yoked to particular experiences of disclosure, in this case to criminal justice personnel, community-based providers, or informal supports. The utility of this modified administration and scoring of the SRQ and the importance of considering reactions across different groups are described.